(untitled) (Indian Journal of Animal Production and Management, 2024)
This study investigated the impact of nano vitamin E with Selenium on serum parameters in Japanese quails. The experiment involved three groups: a control group (C1) fed a basal diet, a T1 group receiving vitamin E (150mg/kg) and Selenium (0.3mg/kg), and a T2 group receiving nano vitamin E (15mg/kg) and Selenium (0.03mg/kg). Results revealed significant differences (p<0.05) in serum analyses among the groups. The T2 group showed the highest total protein and globulin levels, while the T1 group exhibited the highest total albumin levels. Total cholesterol levels were significantly lower in the T2 group, with the highest HDL cholesterol. LDL cholesterol levels were lower in the T2 group. SGOT and SGPT levels were significantly lower in the T2 group. These findings suggest the potential benefits of nano vitamin E with Selenium in modulating serum biochemistry in Japanese quails.